CHANGES IN CLINICAL-PHYSIOLOGICAL AND BLOOD MORPHOBIOCHEMICAL PARAMETERS DURING THE DEVELOPMENT OF BROILER CHICKS - Bozorov, J.A.; Yunusov, X.B. (Research Focus International Scientific Journal, 2026)
This article analyzes the clinical and physiological indicators of broiler chicks by age. Changes in morphological and biochemical parameters of blood, body temperature, heart rate, respiratory rate, live weight gain and height growth in broiler chicks depending on the developmental stages in poultry farming conditions were studied. The results of the study are of great importance for effective broiler care, development of optimal feeding systems, and prevention of diseases.